Something Black and White = Kuch Kala Aur Sufaid - Rumana Husain; Illustrated by Priya Kuriyan (Karachi Oxford University Press, 2017)
Three-year-old Anya is very fond of singing but five-year-old Sonia does not enjoy her younger sister's out-of-tune songs. One day Mother and Father bring a special gift for them inside the large box is something black and white...What could it be?
Include Illustrations.
Keywords: Short English Stories -- Short Urdu Subtitles Stories -- Short Stories -- Pakistan Oxford Books